Online Learning for EFL Learners: Perceptions, Challenges, and Expectations - Siti Suharsih; Murti Ayu Wijayanti (Journal of English Language Studies, 2021)
This article discusses EFL learnersâ€™ perceptions, challenges and expectations on online learning during Covid-19 pandemic. Â The participants of this study were the second semester students of Magister of English Study Program in one public university in Banten. Questionnaire and interview were conducted to collect the data. The data were then analyzed qualitatively based on the themes. The research results show that the students perceived positively on the usefulness and the ease of use of online learning. They gave positive responses on online learning in terms of learning autonomy, discipline, technological skill, flexibility, accessibility, and their readiness dealing with technical things. The challenges they faced were dealing with the poor internet connection, motivation dynamics and learning material understanding difficulty. Finally, to deal with the challenges, they expected to have more well-prepared lecturers regarding technological capacity, course content and assessment.